1998
DOI: 10.1046/j.1471-4159.1998.70020752.x
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Exposure During a Critical Period of Development Leads to Persistent Changes in Nicotinic Acetylcholine Receptors of Adult Rat Brain

Abstract: Effects of neonatal nicotine exposure on the development of nicotinic acetyicholine receptor (nAChR) a2, a3, cr4, cs7, and /32 subunit mRNAs and the number of nAChR isoforms in rat brain were studied. The mRNA levels for nAChR subunits were measured by ribonuclease protection assay, and the number of nAChR isoforms was measured with (-)-[ 3H]nicotine, [3H]epibatidine, and ct-[3H}bungarotoxin ([3H]a-Bgt). Pups were divided into two groups: One group received (-)nicotine treatment (0.1 mg/kg s.c. free base twice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 58 publications
2
55
1
Order By: Relevance
“…Similarly, the up-regulation of nAChRs is reported to be induced in the central nervous system of experimental animals chronically treated with nicotine (38,39,58) and neural cells exposed to nicotine (13,59) when examined by a receptor binding assay using [ 3 H]nicotine as a radiolabeled ligand.…”
Section: Camentioning
confidence: 94%
“…Similarly, the up-regulation of nAChRs is reported to be induced in the central nervous system of experimental animals chronically treated with nicotine (38,39,58) and neural cells exposed to nicotine (13,59) when examined by a receptor binding assay using [ 3 H]nicotine as a radiolabeled ligand.…”
Section: Camentioning
confidence: 94%
“…Other studies focusing on receptor expression also showed upregulation of nAChR binding sites, mostly α4β2* nAChRs (Sugiyama et al, 1985;Cairns and Wonnacott, 1988;van de Kamp and Collins, 1994;Miao et al, 1998;Eriksson et al, 2000;Mugnaini et al, 2002a). Thus, morphological and molecular changes in hippocampus and cerebellum in response to developmental nicotine exposure could very well contribute to decreased cognitive performance in the off-spring, and could be even more robust after postnatal exposure when hippocampus and cerebellum are still forming.…”
Section: Introductionmentioning
confidence: 96%
“…Neuronal intrinsic membrane properties also change rapidly during this period (Metherate and Aramakis 1999). Thus, as in other sensory cortices, this is a time of rapid change during which the development of neural circuitry may be particularly sensitive to external in¯uences, i.e., a potential critical period (Miao et al 1998;Aramakis et al 2000).…”
Section: Introductionmentioning
confidence: 99%